Oral health status among health personnel of primary health centers in Mathura district - Vivek Sharma; Navin Anand Ingle; Navpreet Kaur; Pramod Yadav; Ekta Ingle (Wolters Kluwer Medknow Publications, 2016)
Introduction: Health is dynamic and multifactorial in nature. Oral health is an integral part of general health. Health personnel, especially in primary health centers (PHCs), can play an important role in grooming health in their patients. Aim: The aim of this study was to assess the oral health status of health personnel of PHCs. Materials and Methods: A cross-sectional study was carried out among 520 health personnel working in PHCs of Mathura district in the month of September-October 2014. The WHO Oral Health Assessment Form (2013) was used to collect data from each subject. Comparison of oral health status of various health personnel was also done. Results: In the present study, 45 (8.7%) belonged to the upper socioeconomic class, 295 (56.7%) were from upper-middle socioeconomic class, and 180 (34.6%) were from lower-middle socioeconomic class. The mean decayed missing filled teeth was 1.11 ± 2.63 for doctors, 1.24 ± 3.10 for pharmacists, 1.10 ± 3.55 for lab technicians, 1.78 ± 3.80 for ward boys/ward nurses, 0.25 ± 0.50 for lady health visitors, and 1.53 ± 3.16 for auxiliary nurse midwives. The difference among study subjects according to occupation was statistically significant (P = 0.787). Conclusion: The oral health status of health personnel of Mathura district was moderate. These health workers can serve as a valuable resource for population-based health promotion approaches in achieving health for all.